Neurological soft signs in antisocial men and relation with psychopathy. (30th June 2016) - Demirel, Omer Faruk; Demirel, Aysegul; Kadak, Muhammed Tayyib; Emül, Murat; Duran, Alaattin
Abstract: Neurological soft signs (NSS) were studied in some axis-I disorders like schizophrenia, obsessive compulsive disorder, bipolar disorder, alcohol and substance abuse disorder. Aim of this study is detection of neurological soft signs in antisocial personality disorder and relation of these signs with psychopathy. The study was included 41 antisocial men and 41 healthy control subjects. Sociodemographic form, neurological evaluation scale and Hare psychopathy checklist was applied to the antisocial subjects, whereas sociodemographic form and neurological evaluation scale were applied to the controls. Antisocial men exhibited significiantly more NSS in total score and subgroups scales (p<0.05). It was shown that there was a significant association with psychopathy scores and NSS sequencing complex motor tasks (r=0.309; p=0.049) and NSS other tests subgroup scores (r=0.328; p=0.037). Similar relation was also observed in comparison between psychopathy subgroups. NSS accepted as being endophenotypes in schizophrenia, were also detected in antisocial group significantly more than controls in our study. Significant relationship between psychopathy and NSS may also hint the role of genetic mechanisms in personality development, though new extended studies with larger sample size are needed for clarification of this relationship. Highlights: Neurological soft signs were significiantly higher for antisocial than healthy controls. Among antisocial group, higher psyschopaths had more neurological soft signs. Neurological soft signs and PCL-R scores were positively correlated.